The voice that challenged a nation : Marian Anderson and the struggle for equal rights - Freedman, Russell (New York : Clarion Books, 2004)
Tells the life story of singer Marian Anderson, describing her famous 1939 Lincoln Memorial performance and explaining how she helped end segregation in the American arts after being refused the right to perform at Washington's Constitution Hall because of the color of her skin.
Easter Sunday, April 9, 1939 -- Twenty-five cents a song -- A voice in a thousand -- Marian fever -- Banned by the DAR -- Singing to the nation -- Breaking barriers -- "What I had was singing.".
Includes bibliographical references (p. 95-103), discography (p. 105-106), and index.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
8.2
5-8
Keywords: Anderson, Marian, -- 1897-1993 -- Juvenile literature; Anderson, Marian, -- 1897-1993.; Anderson, Marian, -- 1897-1993.; African American singers -- Biography -- Juvenile literature; African Americans -- Civil rights -- Juvenile literature; Contraltos -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Singers; Women -- Biography; African Americans -- Biography; Singers -- Biography; Women -- Biography